Peningkatan Motivasi dan Prestasi Melalui Model Pembelajaran Make a Match Berbantuan Ice Breaking Kelas V SD - Apriani, Syntia; Juarsa, Osa; Alexon (JURIDIKDAS, 2024)
This research aims to describe the application of the Make a Match type cooperative learning model assisted by Ice Breaking to increase the motivation and learning achievement of class V students in thematic learning at SDN 09 Bermani Ilir. This research is Classroom Action Research. The subjects in this research were teachers and students of class V primary school 09 Bermani Ilir. The research instruments are observation sheets, test sheets, and motivation questionnaires. The test data analysis technique uses the average formula and percentage of classical learning completeness. The learning motivation questionnaire data was analyzed by determining the maximum score and minimum score. The research results showed that from the results of the student learning motivation questionnaire in cycle I, the average was 57.55 in the high category and in cycle II the average was 62.4 in the high category. Meanwhile, the average learning achievement of IPS cycle I students obtained an average score of 78.15 with classical learning completeness of 73.68%. The second cycle of IPS obtained an average score of 85 with classical learning completeness of 94.73%. Meanwhile, Indonesian language cycle I obtained an average score of 71.84 with classical learning completeness of 73.68%. Cycle II Indonesian obtained an average score of 79.47 with classical learning completeness of 89.47%. It was concluded that the application of the Make a Match type cooperative learning model assisted by Ice Breaking could increase student motivation and learning achievement in thematic learning in class V at primary school 09 Bermani Ilir.